Aspects of Feminist Writing: A Presentation of Common Issues - Meenakshi Sharma Yadav; Manoj Kumar Yadav (Journal of English Language Teaching and Linguistics, 2018)
Feminist literary criticism is a literary criticism knowledgeable by feminist theory, or, more broadly, by the politics of feminism. It uses feminist principles and ideology to critique the language of literature. This school of thought seeks to analyze and describe the ways in which literature portrays the narratives of male domination by exploring the economic, social, political, and psychological forces embedded within literature. Feminism emerged as an important force in the western world in 1960s when women realized the attitude of their male colleagues who swore about equality, was actually the strategy used by them to keep women subservient, then a revolution by women to fight against them, and against racism and sexism was felt. This awakening spread over and as a result feminist criticism emerged on as an off –shoot of women’s Liberation Movement. Beginning with the interrogation of male-centric literature that portrayed women in a demeaning and oppressed model, theorist such as Marry Ellman, Kate Millet and Germaine Greer challenged past imaginations of the feminine within literary scholarship. It is very important for us to know that who these women writers are, what did they write and what were the sources of their writings. The present paper focuses on some of the above said important aspects of feminist writings and some of famous feminist writers also.